Interpreting and Utilising Intersubject Variability in Brain Function - Seghier, Mohamed L.; Price, Cathy J. (Trends in cognitive sciences, 2018)
We consider between-subject variance in brain function as data rather than noise. We describe variability as a natural output of a noisy plastic system (the brain) where each subject embodies a particular parameterisation of that system. In this context, variability becomes an opportunity to: (i) better characterise typical versus atypical brain functions; (ii) reveal the different cognitive strategies and processing networks that can sustain similar tasks; and (iii) predict recovery capacity after brain damage by taking into account both damaged and spared processing pathways. This has many ramifications for understanding individual learning preferences and explaining the wide differences in human abilities and disabilities. Understanding variability boosts the translational potential of neuroimaging findings, in particular in clinical and educational neuroscience. A wealth of scientifically and clinically relevant information is hidden, and potentially invalidated, when data are averaged across subjects. There is growing interest in using neuroimaging to explain differences in human abilities and disabilities. Progress in this endeavour requires us to treat intersubject variability as data rather than noise. Our plastic and noisy brains intrinsically change the parameterisation of each individual’s brain, providing a rich opportunity to understand differences in brain function. Normal variability can be used to decode different neural pathways that can sustain the same task (degeneracy). This is of paramount importance for understanding why patients have variable outcomes after damage to seemingly similar brain regions.